2019
DOI: 10.1302/2046-3758.84.bjr-2018-0291.r1
|View full text |Cite
|
Sign up to set email alerts
|

Synovial fluid interleukin-16, interleukin-18, and CRELD2 as novel biomarkers of prosthetic joint infections

Abstract: Objectives Prosthetic joint infection (PJI) diagnosis is a major challenge in orthopaedics, and no reliable parameters have been established for accurate, preoperative predictions in the differential diagnosis of aseptic loosening or PJI. This study surveyed factors in synovial fluid (SF) for improving PJI diagnosis. Methods We enrolled 48 patients (including 39 PJI and nine aseptic loosening cases) who required knee/hip revision surgery between January 2016 and December 2017. The PJI diagnosis was established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…We confirmed that SF IL-16 can be used as a biomarker for PJI diagnosis [10]. To date, no studies have reported the possible effects of IL-16 on bone.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…We confirmed that SF IL-16 can be used as a biomarker for PJI diagnosis [10]. To date, no studies have reported the possible effects of IL-16 on bone.…”
Section: Discussionsupporting
confidence: 81%
“…Abu-Ame [41] confirmed that LPS-induced osteoclastogenesis is mediated by TNF or its p55 receptor in vivo. Because we detected increased IL-16 levels in patients with PJI [10], whether IL-16 inhibition improves GN bacterial infection-associated bone loss warrants further study. In this study, the anti-IL-16 antibody treatment prevented LPS-induced trabecular bone loss and osteoclast activation in vivo.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This is the reason other ILs such as IL-16, IL-18, and cysteine rich with EGF-like domains 2 (CRELD2) are being investigated as better indicators. Chen et al [46] found that IL-16 and IL-18 and CRELD2 had statistical significance as overall better indicators in PJI detection than CRP and leukocyte count.…”
Section: Biomarkersmentioning
confidence: 99%